Simulation of location and size effects on performance adjustment in hybrid N-type MOSFETs. (1st June 2020) - Liu, Renhua; Sun, Yabin; Huang, Qin; Li, Xiaojin; Shi, Yanling; Wang, Changfeng; Liao, Duanquan; Tian, Ming; Liu, Ziyu
Abstract: In this letter, a change-flexibly-SELBOX-based FDSOI MOSFET, named hybrid device, is proposed, and the dependence of the open window's size and location on the thermal and electrical characteristics is investigated with technology computer-aided design (TCAD) simulation. An extensive comparative analysis of the key characteristics in hybrid device, FDSOI MOSFET without back bias (BB), and FDSOI MOSFET with BB have been performed. When the open window locates under the junction between channel and drain extension, the hybrid device is found to be most thermally efficient, compared to FDSOI MOSFET with/without BB and hybrid device with other window condition. Besides, the electrical characteristics in hybrid device strongly depend on the size and location of the open window, when the doping type of back plane (BP) is similar to source/drain region. The critical parameters, such as current density, electric potential, potential contours, electron mobility and density, are characterized and compared to investigate the underlying physical mechanisms. It reveals that the elevated electrostatic potential near SOI/BOX interface through the open window contributes to the observed electrical performance in hybrid device.